2000
DOI: 10.1074/jbc.m005129200
|View full text |Cite
|
Sign up to set email alerts
|

A Reaction-induced Fourier Transform-Infrared Spectroscopic Study of the Lactose Permease

Abstract: In chemiosmotic coupling, a transmembrane ion gradient is used as the source of energy to drive reactions. This process occurs in all cells, but the microscopic mechanism is not understood. Here, Escherichia coli lactose permease was used in a novel spectroscopic method to investigate the mechanism of chemiosmotic coupling in secondary active transporters. To provide a light-triggered electrochemical gradient, bacteriorhodopsin was co-reconstituted with the permease, and reaction-induced Fourier transform-infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Therefore, we assessed the water content of our samples by calculating the ratio of the absorbance at 3290 cm ÿ1 (water plus protein contributions) to the absorbance at 1545 cm ÿ1 (protein contributions). The ratio was derived from each FT-IR absorption spectrum (Patzlaff et al, 2000). The average ratios for the 2-h, 1-h, and 20-min data sets were indistinguishable and were 2.15 1 0.35, 2.22 1 0.40, and 2.13 1 0.39, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we assessed the water content of our samples by calculating the ratio of the absorbance at 3290 cm ÿ1 (water plus protein contributions) to the absorbance at 1545 cm ÿ1 (protein contributions). The ratio was derived from each FT-IR absorption spectrum (Patzlaff et al, 2000). The average ratios for the 2-h, 1-h, and 20-min data sets were indistinguishable and were 2.15 1 0.35, 2.22 1 0.40, and 2.13 1 0.39, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The bacteriorhodopsin contributions have been subtracted out using an optical measurement of the bacteriorhodopsin and total protein concentrations. 37 The lactose permease spectrum decays in the 5 min following saturating laser flashes (data not shown), presumably with the decay of a component of the proton motive force. A positive vibrational band attributable to the permease is observed at 1734 cm -1 (Figure 15A); this band is tentatively assigned to the CdO stretch of carboxylic acid residues in the permease.…”
Section: Transportmentioning
confidence: 94%
“…130 Bacteriorhodopsin-containing purple membrane was isolated and fused with these liposomes by a freeze-thaw technique. 37 Control experiments on the coreconstituted vesicles demonstrated a stimulation of lactose efflux under illumination and suggested that each permeasecontaining liposome also contained one or more bacteriorhodopsin molecules. 37 These experiments also showed that bacteriorhodopsin was preferentially oriented to pump protons into the liposome (Figure 14).…”
Section: Transportmentioning
confidence: 99%
See 2 more Smart Citations